A Clinical and Procedural Guideline for Gastrointestinal Endoscopy Units during COVID-19 Pandemic Era - Hasan Maulahela; Ari Fahrial Syam; Kaka Renaldi; Muhammad Begawan Bestari; Roy Sutikno; Murdani Abdullah; Marcellus Simadibrata; Dadang Makmun (Acta Medica Indonesiana)
The World Health Organization (WHO) has declared COVID-19 as global pandemic since there are tremendous growing numbers of confirmed cases for SARS-C0V-2 infection, the number of affected countries and high mortality rate. The global COVID-19 pandemic also will affect various aspects of health care including endoscopic service. The Indonesian Society for Digestive Endoscopy (ISDE), which provides a scope for doctors who perform endoscopic procedures, has developed a clinical and procedural guideline that may serve as a reference for doctors performing gastrointestinal endoscopy in Indonesia.